Incidencias del femicidio en el Ecuador y su relación con el contexto de autoidentificación étnica (año 2014 - primer semestre de 2024) - Colcha Quimbia, María del Cisne (2025)
Femicides, as an extreme expression of gender violence, pose a serious problem affecting women from various ethnic groups. Despite its classification in the Comprehensive Organic Criminal Code (COIP), structural gaps persist that hinder effective prevention and sanctioning. The general objective of this study was to analyze the evolution of femicide incidence in Ecuador from 2014 to the first half of 2024, using official statistical sources and specialized literature to identify differences in rates among various self-identified ethnic groups and the factors influencing these results. The research employed a mixed-methods documentary approach, with a descriptive depth level, applying analytical-synthetic and socio-legal methods. Techniques included document review and structured interviews, the latter conducted with a non-probabilistic intentional sample of experts in socio-legal issues. The main findings revealed that, when comparing femicide rates and ethnic distribution, the majority of victims are mestizo women\; those from minority groups face specific vulnerabilities that increase their risk of being attacked. Key factors associated with femicide include sexism, economic and emotional dependency, patriarchal dynamics, and substance abuse. Additionally, failures in the implementation of public policies were identified, such as lack of resources, revictimization, and cultural barriers. It was concluded that the incidence of femicide reflects structural problems related to the lack of prevention policies and socio-cultural dynamics, making it imperative to strengthen public strategies with an inclusive and differentiated approach that addresses the specific vulnerability conditions of each self-identified ethnic group.